SLUT STREET LIFE (STUDY LOCATION ROAD TOWN PEKANBARU TENGKU UMAR) - Fildzah Bakri; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The Purpose of this research is to determine the strategy of street prostitutes in getting customer and the way they interact and have relationships among prostitutes. The research methode to analyze the data in this study is using qualitative analysis. In urban areas, a problem that caused by society is a social problem. The problems that arise because of the diversity of the communities in this urban areas. Whether it's the diversity of race, culture, religion and so forth, among these problems there is the problem of prostitution, the prostitute problems are like mushrooms in the rainy season. Prostitutes are selling sexual services, such as oral sex or sexual intercourse to get the money. Pekanbaru is a crowded city with a lot of activities, although not included in big cities categories, but the capital city of riau is a bustling area with a bus main terminal, With so many crowded places in the downton of Pekanbaru, this is the places that many street prostitutes comes up every night. The majority age of street prostitutes in Pekanbaru is 28-32 years old. They were less educated, most of them was graduated from elementary school and come from  ​​Padang, Sukabumi, Tanjung Balai, Bandung. Furthermore, the majority of street prostitutes is worked individually, with revenue of Rp 100,000 to Rp 300,000 per night. There are so many strategies undertaken by the prostitutes to get customer, some of it is they wear sexy dress, scrubs, wearing wallet powder, herbal drinks, sports, flower bath and some of them also used implant. Interaction between them is very strong, both in terms of positive and negative terms. Interaction that occurs between them, whether it’s cooperation, competition and conflict. The majority of street prostitutes have another job during the day to look for additional money, in the evening they start to hung in the streets. The majority of street prostitutes is working as a street prostitute is for reasons of economic factor and uneducated factor. Keywords: prostitution, interaction, strategy